Motivation in national service training and staff work : the construct, antecedents, and outcomes - Lim, Zhong Hao (2015)
Military conscription, also known as National Service (NS), remains practised in many places worldwide. Yet, sound psychological research on conscripts’ Motivation In NS Training and Staff work (MINTS) remains lacking. In this study, an attempt to introduce a measure of conscripts’ MINTS was made from a self-determination theoretical (Ryan & Deci, 2000) perspective. Possible individual-difference antecedents to MINTS, and outcomes of MINTS were explored. MINTS scale items were developed based on literature review and structured interviews. Eighty-one previously conscripted men from the Singapore Armed Forces provided survey responses to validate the scale. They also filled in measures assessing (a) three personality conscientiousness facets – traditionalism, responsibility, industriousness; (b) two parental upbringing factors – their parents’ encouragement of NS, and whether their parents worked as military regulars; (c) their display of positive military outcomes. Confirmatory factor analysis found three interpretable dimensions of MINTS: amotivation; identified regulation, and intrinsic regulation. Correlational and path analyses revealed the role of individual-differences in contributing to MINTS – traditionalism negatively predicted amotivation, and positively predicted intrinsic regulation; responsibility positively predicted identified regulation; parental encouragement of NS positively predicted both identified and intrinsic regulation. In turn, positive effects were found for identified regulation predicting one’s holding of advocacy attitudes for NS, and intrinsic regulation predicting one’s consideration of a defence-related career. Contextual factors, such as parental influence, may deserve greater attention toward developing MINTS. The study of MINTS has practical implications, and more positive-minded academic focus should be afforded to improve and further its study.